Times of History, Times of Nature : Temporalization and the Limits of Modern Knowledge - Anders Ekström; Staffan Bergwik (Berghahn Books, 2022)
As climate change becomes an increasingly important part of public discourse, the relationship between time in nature and history is changing. Nature can no longer be considered a slow and immobile background to human history, and the future can no longer be viewed as open and detached from the past. Times of History, Times of Nature engages with this historical shift in temporal sensibilities through a combination of detailed case studies and synthesizing efforts. Focusing on the history of knowledge, media theory, and environmental humanities, this volume explores the rich and nuanced notions of time and temporality that have emerged in response to climate change.